GEZ petrol station: CVP analysis and spread sheet modelling for planning and decision making - Ku Ismail, Ku Nor Izah; Wan Hussin, Wan Nordin; Salleh, Mat Supian (Emerald Group Publishing Limited, 2015)
Subject area– Management Accounting and Financial Modelling.Study level/applicability – Undergraduate and post-graduated levels.Case overview– Aiman, the Area Manager of GEZ Berhad, realised the importance for petrol station operators to have an understanding of fundamental management accounting concepts such as cost behaviour and cost–volume–profit (CVP) analysis. He also believed that the petrol station operators should be proficient in using Microsoft Excel functionality and able to construct “intelligent” financial model with extended sensitivity analysis. Being a manager responsible for training the petrol station operators, Aiman would like to introduce the CVP concepts and spreadsheet model-building process to the petrol station operators, to aid them in planning and decision making. To construct the Excel spreadsheet model, Aiman sought the assistance of Rizal, a university lecturer in accounting, who in turn gathered the relevant operational and financial data from Baron Service Station, a typical petrol station under GEZ stable.The model should be flexible enough to allow the petrol station operator to anticipate, for example: What will happen to overall profitability of the petrol station if the fuel prices go up? What is the minimum volume of fuel that needed to be sold to break even? How much extra profit can be generated if credit card sale is reduced? and Is it viable to install an automated teller machines (ATM) kiosk and incurring administrative charges from bank to lure more customers to visit the petrol station? As the petrol station sells multiple products (petrol, diesel and convenience goods), the owner is also interested to know which product lines are the most and least profitable.Thus, the model should be able to generate segmented income statement with appropriate allocation of the common fixed costs to the each of the products.Expected learning – outcomes The case discussion is intended to achieve the following learning outcomes: students are able to prepare a financial model which include a segmented contribution income statement based on the information on product mix; students are able to calculate the break-even point and distinguish between fixed and variable costs; students are able to differentiate between traceable fixed costs and common fixed costs; students are able to build a financial model that is sufficiently flexible to allow various what if analysis to be performed; and students are able to use what if analysis tools in Excel such as Goal Seek and Data Tables. Supplementary materials – Teaching notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes.